2020
DOI: 10.1111/jcmm.15058
|View full text |Cite
|
Sign up to set email alerts
|

Association of PARP1 polymorphisms with response to chemotherapy in patients with high‐risk neuroblastoma

Abstract: The genetic aetiology and the molecular mechanisms that characterize high-risk neuroblastoma are still little understood. The majority of high-risk neuroblastoma patients do not take advantage of current induction therapy. So far, one of the main reasons liable for cancer therapeutic failure is the acquisition of resistance to cytotoxic anticancer drugs, because of the DNA repair system of tumour cells. PARP1 is one of the main DNA damage sensors involved in the DNA repair system and genomic stability. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The prognosis of patients with NB is extremely poor, which accounts for ~12–15% of all pediatric cancer-associated deaths ( 7 , 8 ). In recent years, treatments for low- and medium-risk NB have improved; however, the cure rate for patients with high-risk NB remains low ( 9 , 10 ). It is therefore crucial to develop novel treatments for patients with high-risk NB.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with NB is extremely poor, which accounts for ~12–15% of all pediatric cancer-associated deaths ( 7 , 8 ). In recent years, treatments for low- and medium-risk NB have improved; however, the cure rate for patients with high-risk NB remains low ( 9 , 10 ). It is therefore crucial to develop novel treatments for patients with high-risk NB.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al studied the mechanism of chemotherapeutic drug resistance and found that PARP1 induced the degradation of BRD7, leading to the resistance of cancer cells to DNA damage agents [43]. Avitabile et al found that PARP1 was one of the main DNA damage sensors involved in DNA repair system and genomic stability, and PARP1 expression is closely related to chemotherapy resistance of neuroblastoma [44]. BER is a very important pathway leading to oxaliplatin resistance [45].…”
Section: Discussionmentioning
confidence: 99%
“…The present and previous results (21) indicate that C282Y HFE impacts neuroblastoma characteristics such as therapy resistance and cell proliferation. Several studies reported that single nucleotide polymorphisms (SNPs) in genes [e.g., ATP binding cassette subfamily C member 1 (ABCC1); caspase 8 (CASP8); ERCC excision repair 1, endonuclease non-catalytic subunit/ERCC excision repair 4, endonuclease non-catalytic subunit (ERCC1/XPF or ERCC1/ERCC4); poly(ADP-ribose) polymerase 1 (PARP1); base excision repair (BER); methyltransferase like 14 (METTL14)] are risk factors for neuroblastoma development and patient survival (40)(41)(42)(43)(44)(45). Our data indicate that the frequency of the C282Y HFE SNP in neuroblastoma patients should also be determined in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%